2015
DOI: 10.1093/ntr/ntu339
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to FDA-Proposed Graphic Warning Labels Affixed to U.S. Smokers’ Cigarette Packs

Abstract: U.S. smokers' reactions to graphic warning labels on their own packs were similar to other, more controlled studies. Qualitative findings underscore the need for warning labels that encourage self-referential processing without increasing defensive reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 75 publications
(96 reference statements)
3
39
0
Order By: Relevance
“…31 Another experiment with 202 smokers, published after the meta-analysis search, also showed no effect on behavior. 32 Most large observational studies evaluating smoking behavior before and after warning exposure have found increases in quit attempts and reductions in smoking prevalence in countries that implemented pictorial warnings, 18,19 although some studies have not 33 ; other studies indicate that some of the effects of warnings may partially wear out over time. 34,35 Such studies support only limited inferences about effect, however, because countries often change several policies at the same time; secular trends and historical events are difficult to account for; and potential comparison countries may differ in other important ways.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another experiment with 202 smokers, published after the meta-analysis search, also showed no effect on behavior. 32 Most large observational studies evaluating smoking behavior before and after warning exposure have found increases in quit attempts and reductions in smoking prevalence in countries that implemented pictorial warnings, 18,19 although some studies have not 33 ; other studies indicate that some of the effects of warnings may partially wear out over time. 34,35 Such studies support only limited inferences about effect, however, because countries often change several policies at the same time; secular trends and historical events are difficult to account for; and potential comparison countries may differ in other important ways.…”
Section: Discussionmentioning
confidence: 99%
“…Syntheses of the GHW literature (Hammond, 2011; Noar et al, 2016a, 2016b), coupled with recent experimental evidence (Brewer et al, 2016; Gibson et al, 2015; McQueen et al, 2015), show that such exposure can produce important effects on smoking-related cognitive, affective, and behavioral outcomes. Moreover, our study, together with previous research (Hall et al, 2015; Thrasher et al, 2016), suggests that conversations stimulated by GHW exposure could serve to reinforce and amplify these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to test the effect of multiple exposures over a long period of time. Indeed, a recently published protocol establishes a methodology for testing real-word exposure to cigarette package warnings over time (Brewer et al, 2015), and a study in which smokers carried packages with graphic warnings for one week found that smokers paid more attention to graphic than to text-only warnings, and that five of the nine warnings were associated with greater thoughts of health risks (McQueen et al, 2015). Third, race/ethnicity groups included in this study were limited to white, African American, and Hispanic.…”
Section: Discussionmentioning
confidence: 99%